Hearing loss etiology in patients referring to Isfahan cochlear implantation center - Abtahi, Seyed Hamidreza; Sepehrnejad, Mahsa; Dehghan, Shiva; Nilforoush, Mohammad Hossein (Researcher Bulletin of Medical Sciences, 2018)
Introduction: Hearing loss is the most common congenital disorders occurring among newborn. Identifying the factors affecting it would reduce the incidence of this disorder. Therefore, the aim of this study was to examine the etiology of congenital hearing loss in patients referring to Isfahan Cochlear implantation center. Materials and Method: This study was performed on 689 patients with cochlear implantation. Demographic data and relative frequency of different causes of congenital hearing loss (acquired and genetic) were determined and recorded. T-test, Chi-Square and Mann-Whitney tests were used to compare the variables studied. Results: Our findings showed that 50 patients (7.7%) had history of drug use, 9 (1.3%) had history of taking ototoxic drugs, 99 (14.3%) had history of kernicterus, 157 patients (22.8%) had a history of hyperbilirubinemia, 15 (2.1%) history of meningitis, 57 (8.3%) had a history of seizure, one (0.1%) had a birth weight less than 1500 grams, 4 cases (0.06%) had history of hypoxia, 18 cases (2.6%) had history of trauma, one (0.1%) had CMV history, and one (0.1%) hearing loss due to syndromicity. On the other hand, it was determined that the probable causes of hearing loss were not related to the severity of hearing loss and age of the patients (p <0.05) Conclusion: Although the prevalence of congenital hearing loss is low, it is important to identify and screen for postnatal congenital hearing loss, especially in people with risk factors known in this study, including patients with kernicterus.